Localization–delocalization transition in the Generalized Aubry–André–Harper model in a quasiperiodic superlattice potential - Ullah, Zain; Sajid, Muhammad; Rahim, Amsyar; Umar, Mohd Faudzi; Mohd Shah, Nurisya (Elsevier B.V., 2026)
We investigate localization–delocalization transition in the one-dimensional generalized Aubry–André–Harper (GAAH) model in a quasiperiodic superlattice potential. The critical interplay between the model's two modulated energy scales — the hopping amplitude (t) and the on-site potential (Δ) — generates a rich phase diagram featuring extended, localized, and critical phases. We employ both static spectral and dynamics indicators to identify these phases. In static analysis, we compute the energy spectrum as a function of the common phase ϕ of the modulations and employ the inverse participation ratio (IPR) to map localization–delocalization phase diagram as a function of t and Δ. Dynamically, we model the evolution of an initially localized quantum state as a continuous-time quantum walk (CTQW), analyze the resulting probability distribution and time-dependent IPR to corroborate the static results. This work establishes a direct correspondence between static spectral indicators and dynamics, providing a unified framework for characterizing localization in quasiperiodic systems. Our findings offer new perspectives for controlling quantum transport in engineered quantum platforms.